Reconceptualizing Autonomy for Bioethics - Dive, Lisa; Newson, Ainsley J (Kennedy Institute of Ethics journal, 2018)
Autonomy plays a central role in bioethics, but there is no consensus as to how we should understand this concept. This paper critically considers three different conceptions of autonomy: the default conception prevalent in bioethics literature; a broader procedural account of autonomy drawing on moral philosophical approaches; and a substantive, perfectionist account. Building on Rebecca Walker's critique of the default conception of autonomy, we will argue that a substantive, perfectionist approach both fulfils Walker's criteria for a conception of autonomy in bioethics and lends itself to application in practical scenarios. In so doing, we draw on scenarios from genomic medicine to show that a substantive, perfectionist approach not only offers a more conceptually adequate understanding of autonomy in more complex cases, but also lends itself to practical application by helping health professionals identify how they can maximize people's capacity to exercise their autonomy.